2012
DOI: 10.1039/c2cp23146h
|View full text |Cite
|
Sign up to set email alerts
|

Confinement effects in the hydrogen adsorption on paddle wheel containing metal–organic frameworks

Abstract: The confinement effects upon hydrogen adsorption in Cu(II)-paddle wheel containing metal-organic frameworks (MOFs) were evaluated and rationalized in terms of the structural properties (cavity types and pore diameters) of PCN-12, HKUST-1, MOF-505, NOTT-103 and NOTT-112. First-principles calculations were employed to identify the strongest adsorption positions at the paddle wheel inorganic building unit (IBU). The adsorption centres due to confinement were located through analysis of 3D occupancy maps obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…As we know, molecular structures and reactions occurring inside of the channel are influenced by confinement, whereas there has no such effect on the outer surface of channel123456789101112131415161718192021222324252627282930313233343536373839. It seems that it is quite difficult to describe the reaction in and outside of the channel by the same model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we know, molecular structures and reactions occurring inside of the channel are influenced by confinement, whereas there has no such effect on the outer surface of channel123456789101112131415161718192021222324252627282930313233343536373839. It seems that it is quite difficult to describe the reaction in and outside of the channel by the same model.…”
Section: Discussionmentioning
confidence: 99%
“…Why does confinement influence the reaction in channels? Theoretical researches have revealed that confinement can change the interactions between reactant and catalyst31323334353637. Confinement can also influence the electronic structure of catalyst in channel2324252627282930.…”
mentioning
confidence: 99%
“…For example, Sastre and co-workers used a similar flavour of DFT-D to investigate the adsorption of hydrogen at the unsaturated copper centres of Cu 3 (btc) 2 , obtaining an interaction energy of −10.8 kJ mol −1 . 53 Kong et al employed the non-empirical vdW-DF functional to study the adsorption of H 2 in Zn 2 (bdc) 2 (ted), a system without accessible metal sites, and arrived at energies between −10 and −11 kJ mol −1 for the strongest interaction sites. 54 Experimentally, both these systems exhibit isosteric heats of hydrogen adsorption that are slightly higher than those observed for ZIF-8, ranging between 5 and 7 kJ mol −1 .…”
Section: ) Geometry Optimisation Of Pristine Frameworkmentioning
confidence: 99%
“…Taking H 2 uptake in MOFs as an example, the interactions between the porous MOF materials and H 2 molecules mainly come from van der Waals interactions, which can be improved by the small pore confined within MOFs. [132] However, most pores cannot be fully utilized under mild temperatures due to weak van der Waals interactions between H 2 and pore surfaces. Strong adsorption sites should be incorporated into the pores for their strongest interactions with hydrogen molecules to enhance the H 2 uptake by designing MOFs with specific micropores and open metal sites.…”
Section: Microenvironment Modulated Catalysismentioning
confidence: 99%